Effect of Exercise Interventions on Health-Related Quality of Life After Stroke and Transient Ischemic Attack: A Systematic Review and Meta-Analysis. Issue 7 (27th May 2021) - Ali, Ali; Tabassum, Dina; Baig, Sheharyar S.; Moyle, Bethany; Redgrave, Jessica; Nichols, Simon; McGregor, Gordon; Evans, Katherine; Totton, Nikki; Cooper, Cindy; Majid, Arshad
Abstract : Supplemental Digital Content is available in the text. Abstract : Exercise interventions have been shown to help physical fitness, walking, and balance after stroke, but data are lacking on whether such interventions lead to improvements in health-related quality of life (HRQoL). In this systematic review and meta-analysis, 30 randomized controlled trials (n=1836 patients) were found from PubMed, OVID MEDLINE, Web of Science, CINAHL, SCOPUS, The Cochrane Library, and TRIP databases when searched from 1966 to February 2020 that examine the effects of exercise interventions on HRQoL after stroke or transient ischemic attack. Exercise interventions resulted in small to moderate beneficial effects on HRQoL at intervention end (standardized mean difference, −0.23 [95% CI, −0.40 to −0.07]) that appeared to diminish at longer-term follow-up (standardized mean difference, −0.11 [95% CI, −0.26 to 0.04]). Exercise was associated with moderate improvements in physical health (standardized mean difference, −0.33 [95% CI, −0.61 to −0.04]) and mental health (standardized mean difference, −0.29 [95% CI, −0.49 to −0.09]) domains of HRQoL while effects on social or cognitive composites showed little difference. Interventions that were initiated within 6 months, lasted at least 12 weeks in duration, involved at least 150 minutes per week, and included resistance training appeared most effective. Exercise can lead to moderate beneficial effects on HRQoL and should be considered an integral part of stroke rehabilitation.